(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
This study investigates the functional deterioration in patients with pigmentary retinitis using computer perimetry. A total of 80 patients with pigmentary retinitis and 30 healthy controls underwent detailed ophthalmologic evaluations, including scotoma tests and error assessments through computer perimetry. Findings reveal a progressive increase in scotomas and elevated rates of false positive and false negative responses as the disease advances, highlighting significant impacts on visual function. These results emphasize the importance of advanced imaging technologies like spectral OCT in the early detection and ongoing assessment of morphological changes in pigmentary retinitis.